2017
DOI: 10.1177/2055116917733642
|View full text |Cite
|
Sign up to set email alerts
|

Intubation following high-dose rocuronium in a cat with protracted laryngospasm

Abstract: Case summaryAn 11-year-old spayed female domestic shorthair cat with a history of laryngospasm at induction of general anesthesia presented for dental evaluation and treatment. The cat was premedicated with hydromorphone (0.05 mg/kg) and alfaxalone (0.5 mg/kg) intravenously, pre-oxygenated for 5 mins (3 l/min, face mask) and anesthesia was induced with alfaxalone (to effect) intravenously. Lidocaine (0.1 ml, 2%) was applied topically to the arytenoid cartilages following loss of jaw tone. Laryngospasm was not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…1,2 The use of NMBAs during intubation has also been evaluated in cats, showing that placement of the tracheal tube is facilitated with these agents. [3][4][5] However, non-depolarizing NMBAs at the doses commonly used almost invariable result in apnea of long duration, which may increase the risk of hemoglobin desaturation during induction and require the institution of positive pressure ventilation for prolonged periods. 4 A recent dose-finding study in a laboratory setting evaluating the NMBA rocuronium in cats showed that reducing the dose of this agent from 0.6 to 0.3 mg/kg intravenously (IV) can significantly limit the time of apnea while preserving the ability to blunt laryngospasm in response to laryngeal stimulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The use of NMBAs during intubation has also been evaluated in cats, showing that placement of the tracheal tube is facilitated with these agents. [3][4][5] However, non-depolarizing NMBAs at the doses commonly used almost invariable result in apnea of long duration, which may increase the risk of hemoglobin desaturation during induction and require the institution of positive pressure ventilation for prolonged periods. 4 A recent dose-finding study in a laboratory setting evaluating the NMBA rocuronium in cats showed that reducing the dose of this agent from 0.6 to 0.3 mg/kg intravenously (IV) can significantly limit the time of apnea while preserving the ability to blunt laryngospasm in response to laryngeal stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The use of NMBAs during intubation has also been evaluated in cats, showing that placement of the tracheal tube is facilitated with these agents. 35 However, non-depolarizing NMBAs at the doses commonly used almost invariable result in apnea of long duration, which may increase the risk of hemoglobin desaturation during induction and require the institution of positive pressure ventilation for prolonged periods. 4…”
Section: Introductionmentioning
confidence: 99%